Phytocompounds in Precision Dermatology: COX-2 Inhibitors as a Therapeutic Target in Atopic-Prone Skin - Muhammad Suleman; Abrar Mohammad Sayaf; Chiara Moltrasio; Paola Maura Tricarico; Francesco Giambuzzi; Erika Rimondi; Elisabetta Melloni; Paola Secchiero; Annalisa Marcuzzi; Angelo Valerio Marzano; Sergio Crovella (Biomolecules)
Atopic dermatitis (AD) is a chronic, multifactorial inflammatory skin disease characterized by persistent pruritus, immune system dysregulation, and an increased expression of cyclooxygenase-2 (COX-2), an enzyme that plays a central role in the production of prostaglandins and the promotion of inflammatory responses. In this study, we employed a comprehensive computational pipeline to identify phytocompounds capable of inhibiting COX-2 activity, offering an alternative to traditional non-steroidal anti-inflammatory drugs. The African and Traditional Chinese Medicine natural product databases were subjected to molecular screening, which identified six top compounds, namely, Tophit1 (−16.528 kcal/mol), Tophit2 (−10.879 kcal/mol), Tophit3 (−9.760 kcal/mol), Tophit4 (−9.752 kcal/mol), Tophit5 (−8.742 kcal/mol), and Tophit6 (−8.098 kcal/mol), with stronger binding affinities to COX-2 than the control drug rofecoxib (−7.305 kcal/mol). Molecular dynamics simulations over 200 ns, combined with MM/GBSA binding free energy calculations, consistently identified Tophit1 and Tophit2 as the most stable complexes, exhibiting exceptional structural integrity and a strong binding affinity to the target protein. ADMET profiling via SwissADME and pkCSM validated the drug-likeness, oral bioavailability, and safety of the lead compounds, with no Lipinski rule violations and favorable pharmacokinetic and toxicity profiles. These findings underscore the therapeutic potential of the selected phytocompounds as novel COX-2 inhibitors for the management of atopic-prone skin and warrant further experimental validation.